Highly selective hydrogenation of arenes over Rh nanoparticles immobilized on α-Al2O3 support at room temperature. (15th April 2023) - Jiang, Wei; Cao, Jing-Pei; He, Zi-Meng; Zhu, Chen; Feng, Xiao-Bo; Zhao, Xiao-Yan; Zhao, Yun-Peng; Bai, Hong-Cun
Graphical abstract: Highlights: Selective hydrogenation of arenes is achieved at room temperature over Rh/α-Al2 O3 . Rh-1/α-Al2 O3 exhibits the highest performance for the conversion of DPE and toluene. The metal Rh nanoparticles are distributed on α-Al2 O3 for Rh-1/α-Al2 O3 . The strong adsorption capacity of toluene and guaiacol occurs on Rh (2 0 0). The routes for the hydrogenation of DPE, toluene and guaiacol are presented. Abstract: Selective hydrogenation of arenes is a crucial process not only for the hydrogen storage and transport but also for the synthesis of important pharmaceutical intermediates. Herein, a series of α-Al2 O3 -supported catalysts prepared using different metals were tested for the arenes hydrogenation of lignin derivatives at room temperature. The kinetic studies reveal that Rh-1/α-Al2 O3 exhibits both the highest reaction rate and TOF value for the conversion of diphenyl ether and toluene. The XRD, TEM, XPS and XAS characterizations suggest that the metal Rh nanoparticles dispersed on α-Al2 O3 support for Rh-1/α-Al2 O3 catalyst is mainly responsible for the H2 activation/dissociation and subsequent arenes hydrogenation. The density functional theory calculation indicates the stronger adsorption capacity of toluene and guaiacol on Rh (2 0 0) than that on Rh (1 1 1) and Rh (2 2 0). Stable Rh-1/α-Al2 O3 can contribute to the improvement of the arenes hydrogenation of lignin derivatives to produce high-value-added platform chemicals at room temperature.